Wealth Management and Retirement. Issue 2 (25th January 2022) - Turin, Sergey Y.; Fine, Peter; Fine, Neil
Abstract : Summary: The purpose of this publication is to introduce basic financial planning concepts and highlight their use in creating a retirement savings plan. These tools may help young surgeons set their financial targets and create a plan to meet them, whereas surgeons later in their careers may reflect on their choices and implement adjustments, or be inspired to pass on the lessons they learned to the next generation. This publication is limited by design and should be thought of as a primer, not a comprehensive treatise. The topic of personal financial management is as vague as it is broad, and there are many concepts and situations that are outside the scope of this publication. Unique goals, income and expense streams, and risk tolerances necessitate individualized solutions, but there are fundamental concepts listed below that are more universally applicable. The discussion is tailored to the high income stream that plastic surgeons can expect, albeit one that starts relatively late in their careers compared to nonphysician colleagues. There are three foundational principles the reader should take away: having a plan is crucial in achieving any financial goal; starting any savings/investment endeavors as early as possible is as or more important than the amount of capital committed to them; and lastly, individual investors (professional and amateur) have consistently demonstrated an inability to consistently do better than the market over the long run.